Insights into teacher trainees' grammar teaching: a qualitative study - Ismail, Fauziah; Awang, Zubaidah (2008)
Relatively little research has studied the impact and influence of Language Teacher Education (LTE) on teacher trainees’ classroom practices and in particular on grammar teaching. The literature suggests that teacher trainees’ classroom practices are very much influenced by diverse factors like teacher cognition, education experience and social contexts. Therefore, there is a crucial need for teacher educators to be aware of and sensitive to all these factors when designing LTE programmes. This research adopts the qualitative approach to examine the influence of language courses in LTE by tracking the experience of teacher trainees during their practicum and to evaluate how prior grammar courses influenced teacher trainees’ teaching of grammar in the classrooms. It employs observations, interviews and teaching journals as the research instruments which are considered most appropriate for the purpose of the research. Data are obtained from a natural setting with the researcher observing the teacher trainees in the classrooms during their teaching practice are triangulated with interviews and teaching journals. This does not only address the purpose of the research but also allows the researcher to have a better understanding and insight into the actual experiences of the teacher trainees.